HUBUNGAN KECERDASAN VERBAL LINGUISTIK DENGAN KAMAMPUAN MENULIS PUISI SISWA KELAS V SD GUGUS II KECAMATAN TANETE RIATTANG KABUPATEN BONE - Rukayah Rukayah; Abd.Kadir; Mujahidah, Mujahidah; Sudarto, Sudarto (Bajang Institute, 2025)
This research is correlational research which aims to: (1) Describe the verbal linguistic intelligence of class V students at SD Cluster II, Tanete Riattang District, Bone Regency? (2) Describe the ability to write poetry of fifth grade students at SD Cluster II, Tanete Riattang District, Bone Regency? (3) Find out whether there is a significant relationship between verbal linguistic intelligence and the ability to write poetry in class V elementary school cluster II students, Tanete Riattang District, Bone Regency? Data collection techniques use tests. The data that has been obtained is analyzed using descriptive statistics and inferential statistics. The results of descriptive statistical analysis showed that students' verbal linguistic intelligence was in the good category with an average of 68.95 and percentage. Meanwhile, the ability to write poetry is in the good category with an average of 69.44 and the correlation between verbal linguistic intelligence and the ability to write poetry is obtained t count > t table (0.585 > 0.207 and a significance value of 0.000 < 0.05 so H1 is accepted and H0 is rejected The conclusion of the research is that there is a significant relationship between verbal linguistic intelligence and the ability to write poetry in class V elementary school cluster II students, Tanete Riattang District, Bone Regency.